2013
DOI: 10.1210/jc.2013-1764
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Insulin Sensitivity After Human Islet Transplantation for Type 1 Diabetes

Abstract: Islet transplantation results in improved insulin sensitivity mediated by effects at both the liver and skeletal muscle. Modern dosing of glucocorticoid-free immunosuppression with low-dose tacrolimus and sirolimus does not induce insulin resistance in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
4
21
0
1
Order By: Relevance
“…Notably, at 2 to 3 weeks after transplant, insulin sensitivity was unchanged in these animals compared to their naive state before streptozotocin treatment (97,98). Finally, studies 6 to 7 months after human islet transplant treated with low-dose tacrolimus and sirolimus immunosuppression also suggested normal insulin sensitivity at the liver and skeletal muscle (99).…”
Section: Role Of Immunosuppression Agentsmentioning
confidence: 80%
“…Notably, at 2 to 3 weeks after transplant, insulin sensitivity was unchanged in these animals compared to their naive state before streptozotocin treatment (97,98). Finally, studies 6 to 7 months after human islet transplant treated with low-dose tacrolimus and sirolimus immunosuppression also suggested normal insulin sensitivity at the liver and skeletal muscle (99).…”
Section: Role Of Immunosuppression Agentsmentioning
confidence: 80%
“…Plasma glucagon and insulin levels were measured in duplicate by double antibody radioimmunoassays (Millipore, Billerica, MA). We have previously demonstrated that this insulin assay performs reliably in the presence of insulin autoantibodies, except in rare cases of extremely high-titer insulin autoantibodies where assay interference is readily apparent (18). The plasma lactate level was measured in duplicate using an automated lactate analyzer (YSI 2900; Yellow Springs Instruments).…”
Section: Biochemical Analysismentioning
confidence: 99%
“…Previous studies have shown that glucotoxicity could modify IR in patients with T1D with HbA 1c levels above 10% . With decrease of HbA 1c from 8% to 6%, IR improved significantly after islet transplantation, which was attributed to normalization of blood glucose level and restoration of suppression of free fatty acids …”
Section: Discussionmentioning
confidence: 92%